Perlindungan Hukum Konsumen terhadap Kualitas BBM di SPBU dalam Konteks Pengoplosan Pertamax di Indonesia - Ariel Putra Yusriansyah; Dinda Apriandini; Vita Alliciana (Program Studi Ilmu Hukum, Universitas Kuningan, 2025)
This article discusses legal protection for consumers regarding the quality of fuel oil (BBM) at gas stations, particularly in the context of the alleged mixing of Pertamax in Indonesia. This case is suspected to cause state losses and harm consumers due to the practice of mixing RON 90 fuel (Pertalite) into RON 92 (Pertamax) and selling it at a higher price. This article aims to examine legal protection for consumers in the case, as well as to explain consumer rights and legal efforts that can be undertaken to seek compensation. This research uses the library study method by collecting data from literature, regulations, and official news. The results of this study are expected to provide an understanding to the public about the importance of transparency among business actors and legal protection for consumers in fuel transactions